2020
DOI: 10.1177/0391398819899403
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricle assist device pulsatility index at the time of implantation is associated with follow-up pulmonary hemodynamics

Abstract: HeartMate II left ventricular assist device controllers provide data including pulsatility index, reflecting the relationship between pump function and hemodynamics. We propose that a higher pulsatility index at hospital discharge following implant may be associated with less vascular congestion and improved clinical outcomes. A retrospective analysis of 40 patients (age 59.2 ± 10.3 years) supported with the HeartMate II devices was conducted. Data revealed moderate Pearson correlations between pulsatility ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…18–20 This hypothesis was strengthened by the log-file analysis, which showed a decreasing trend in HVAD flow and a significant decrease in HVAD pulsatility in csOGO(+) patients. 3,20–23 Interestingly, we observed a significantly lower HVAD flow at admission for intra-pump thrombosis in the OGO(+) group. In other words, the expected increase in calculated HVAD flow due to the friction induced increase of power consumption caused by the intra-pump thrombosis was lower in patients who developed an acute OGO associated with lysis therapy.…”
Section: Discussionmentioning
confidence: 66%
“…18–20 This hypothesis was strengthened by the log-file analysis, which showed a decreasing trend in HVAD flow and a significant decrease in HVAD pulsatility in csOGO(+) patients. 3,20–23 Interestingly, we observed a significantly lower HVAD flow at admission for intra-pump thrombosis in the OGO(+) group. In other words, the expected increase in calculated HVAD flow due to the friction induced increase of power consumption caused by the intra-pump thrombosis was lower in patients who developed an acute OGO associated with lysis therapy.…”
Section: Discussionmentioning
confidence: 66%
“…As displayed in Figure 9, during AVC, the left ventricle and CF‐LVAD can work in series model (Figure 9B); a significant change in the aortic valve hemodynamics was observed secondary to the pulsatile flow generated from natural ventricular contraction and aortic root pressure 3,13 . It has been established that AVC is associated with arterial pulsatility weakening, vascular wall remodeling, increased inflammatory reaction, gastrointestinal bleeding, and aortic insufficiency (AI) 14–17 . Dobarro et al reported that AVC could cause a decrease in the overall survival rate in patients supported with CF‐LVAD, inducing damage to the left ventricle 18 .…”
Section: Discussionmentioning
confidence: 99%